A Chronology of Ancient Earthquake Damage in the Modena Cathedral (Italy): Integrated Dating of Mortars (14C, Pollen Record) and Bricks (TL). Issue 2 (1st February 2023) - Tirelli, Giulia; Bosi, Giovanna; Galli, Anna; Hajdas, Irka; Lindroos, Alf; Martini, Marco; Maspero, Francesco; Mazzanti, Marta; Olsen, Jesper; Panzeri, Laura; Ringbom, Åsa; Sibilia, Emanuela; et al.
ABSTRACT: The 15th century cross-vaults of the medieval Modena Cathedral (UNESCO site) consist of intricate patches of different masonry portions bound by three types of lime mortars and at least two types of gypsum mortars. Such anomalous structure suggests multiple repair works over time after damaging earthquakes. The absolute dating of lime mortars ( 14 C) and bricks (TL) integrated with the pollen record of mortars allowed to clarify the construction and restoration history of the vaults and to link the repairs to the earthquake chronology for the area. The results reveal that the original construction of the vaults (1404–1454) was carried out using lime mortar binding reused Roman and medieval older bricks. Lime mortar was used also for later repairs caused by earthquakes in the 16th and 17th centuries. Gypsum mortars were then used to entirely rebuild some vaults and to repair others in the 18th and 19th centuries. The study indicates that unexpected damage could be revealed by the detailed chronology of masonry binders. These data represent fundamental steps to implement earthquake risk assessments and strengthening projects of ancient buildings.